Muscle‐specific AMPK β1β2‐null mice display a myopathy due to loss of capillary density in nonpostural muscles. Issue 5 (12th February 2014) - Thomas, Melissa M.; Wang, David C.; D'Souza, Donna M.; Krause, Matthew P.; Layne, Andrew S.; Criswell, David S.; O'Neill, Hayley M.; Connor, Michael K.; Anderson, Judy E.; Kemp, Bruce E.; Steinberg, Gregory R.; Hawke, Thomas J.
ABSTRACT: AMP‐activated protein kinase (AMPK) is a master regulator of metabolism. While Muscle‐specific AMPK β1β2 double‐knockout (β1β2M‐KO) mice display alterations in metabolic and mitochondrial capacity, their severe exercise intolerance suggested a secondary contributor to the observed phenotype. We find that tibialis anterior (TA), but not soleus, muscles of sedentary β1β2M‐KO mice display a significant myopathy (decreased myofiber areas, increased split and necrotic myofibers, and increased centrally nucleated myofibers. A mitochondrial‐ and fiber‐type‐specific etiology to the myopathy was ruled out. However, β1β2M‐KO TA muscles displayed significant ( P <0.05) increases in platelet aggregation and apoptosis within myofibers and surrounding interstitium ( P <0.05). These changes correlated with a 45% decrease in capillary density ( P <0.05). We hypothesized that the β1β2M‐KO myopathy in resting muscle resulted from impaired AMPK‐nNOSμ signaling, causing increased platelet aggregation, impaired vasodilation, and, ultimately, ischemic injury. Consistent with this hypothesis, AMPK‐specific phosphorylation (Ser1446) of nNOSμ was decreased in β1β2M‐KO compared to wild‐type (WT) mice. The AMPK‐nNOSμ relationship was further demonstrated by administration of 5‐aminoimidazole‐4‐carboxamide 1‐β‐D‐ribofuranoside (AICAR) to β1β2‐MKO muscles and C2C12 myotubes. AICAR significantly increased nNOSμ phosphorylation and nitric oxide production ( P <0.05) within minutes of administration in WT muscles and C2C12 myotubes but not in β1β2M‐KO muscles. These findings highlight the importance of the AMPK‐nNOSμ pathway in resting skeletal muscle.—Thomas, M. M., Wang, D. C., D'Souza, D. M., Krause, M. P., Layne, A. S., Criswell, D. S., O'Neill, H. M., Connor, M. K., Anderson, J. E., Kemp, B. E., Steinberg, G. R., and Hawke, T. J. Musclespecific AMPK β1β2‐null mice display a myopathy due to loss of capillary density in nonpostural muscles. FASEB J . 28, 2098–2107 (2014). www.fasebj.org